Evaluation of novel fungicides (FRAC groups 7, 9, 12) for managing cranberry fruit rot - Uppala, Leela Saisree; Sulley, Salisu (Frontiers in Plant Science, 2025)
Cranberry fruit rot (CFR) is a major disease complex that significantly impacts cranberry crops, leading to substantial yield losses. Over the past decade, CFR has become increasingly problematic, particularly in high-yielding and newer cultivars, with reported losses ranging from 50% to 100%. Additionally, the cranberry industry faces increasing restrictions on the use of broad-spectrum fungicides, such as chlorothalonil and mancozeb, necessitating the exploration of alternative management strategies. This study, conducted from 2021 to 2024 at the University of Massachusetts-Amherst Cranberry Station, evaluated novel fungicides from FRAC Groups 7, 9, and 12. The active ingredients—benzovindiflupyr, pydiflumetofen, cyprodinil, and fludioxonil—were tested individually and in combination with azoxystrobin (FRAC 11). The efficacy of these fungicides in reducing CFR incidence and improving yield was assessed on cranberry cultivars ‘Demoranville’, ‘Ben Lear,’ and ‘Stevens’ with applications made at early, mid, and late bloom stages. Significant differences in fruit rot incidence and yield were observed in 2021, 2023 and 2024. Treatments containing pydiflumetofen, pydiflumetofen & fludioxonil, and benzovindiflupyr, when applied in combination with azoxystrobin, consistently resulted in lower rot incidence and higher yields. The treatment containing cyprodinil & fludioxonil plus azoxystrobin, tested only in 2021, also resulted in lower rot incidence and higher yield. These findings highlight the potential of novel fungicides from FRAC Groups 7, 9, and 12 as effective alternatives for CFR management. Their use could diversify the CFR management toolkit, mitigate fungicide resistance, and reduce environmental impacts, addressing the challenges posed by increasing fungicide regulations.